Incidence of hepatocellular carcinoma and mortality in chronic viral hepatitis in an Asian population with and without HIV infection - Lui, Grace Chung‐Yan; Hui, Vicki Wing‐Ki; Sze, Shun‐Fung; Wong, Bonnie Chun‐Kwan; Cheung, Catherine; Lee, Man‐Po; Yip, Terry Cheuk‐Fung; Tse, Yee‐Kit; Lai, Jimmy Che‐To; Chan, Henry Lik‐Yuen; Wong, Vincent Wai‐Sun; Hui, Yee‐Tak; et al. (Alimentary pharmacology & therapeutics, 2023)
It is uncertain whether people with HIV infection have a higher incidence of hepatocellular carcinoma (HCC) than the general population. To compare the incidence of HCC between people infected with HBV and/or HCV with and without HIV METHODS: We performed a retrospective population-based cohort study, involving people with HBV and/or HCV infection from 2001 to 2018. The primary endpoint was incidence of HCC; secondary endpoint was all-cause mortality. We performed Cox proportional hazard regression models to estimate the hazard ratios (HR) of HIV for the primary and secondary endpoints. We identified 1374 people infected with HIV and 39,908 people without HIV with HBV and/or HCV infection. Among those with HIV, 654 (47.6%) had HBV, 649 (47.2%) HCV and 71 (5.2%) HBV-HCV-co-infection; they were younger, and had a higher prevalence of HCV and a lower prevalence of cirrhosis. The incidence rate estimates of HCC were, respectively, 1.5 (95% CI: 0.8-2.5) and 7.6 (95% CI 7.3-8.0) per 1000 person-years for those with and without HIV infection. Using multivariate Cox proportional hazard regression models, among people with HBV, HIV was associated with lower risk of HCC (adjusted HR: 0.376, 95% CI: 0.201-0.704, p = 0.01) and death (adjusted HR: 0.692, 95% CI: 0.552-0.867, p = 0.007). Risks of HCC were similar for HCV and HBV-HCV co-infection for people with and without HIV. Among individuals with HBV infection, the Incidence of HCC was lower in those with HIV. For HCV infection, incidence of HCC was similar between those with and without HIV.